2016
DOI: 10.1155/2016/9525724
|View full text |Cite
|
Sign up to set email alerts
|

Immune Mediators in Osteoarthritis: Infrapatellar Fat Pad-Infiltrating CD8+ T Cells Are Increased in Osteoarthritic Patients with Higher Clinical Radiographic Grading

Abstract: Osteoarthritis is a condition of joint failure characterized by many pathologic changes of joint-surrounding tissues. Many evidences suggest the role of both innate and adaptive immunity that interplay, resulting either in initiation or in progression of osteoarthritis. Adaptive immune cells, in particular T cells, have been demonstrated to play a role in the development of OA in animal models. However, the underlying mechanism is yet unclear. Our aim was to correlate the frequency and phenotype of tissue-infi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 39 publications
3
29
0
Order By: Relevance
“…In a report by Penatti et al (2017), they have reported a higher CD4/CD8 T cell ratio in the peripheral blood of patients with OA as compared to healthy donors; however, the CD8 T cell frequencies seemed to be higher in the SF of patients with OA as compared to the peripheral blood which corroborates with our results as well . Similar results were reported in another study where an increased proportion of CD8+ T cells within the synovial tissue was found as compared to proportions in the circulating peripheral blood . We also observed a decreased infiltration of CD8+ T cells as the disease progressed to advanced stage.…”
Section: Discussionsupporting
confidence: 92%
“…In a report by Penatti et al (2017), they have reported a higher CD4/CD8 T cell ratio in the peripheral blood of patients with OA as compared to healthy donors; however, the CD8 T cell frequencies seemed to be higher in the SF of patients with OA as compared to the peripheral blood which corroborates with our results as well . Similar results were reported in another study where an increased proportion of CD8+ T cells within the synovial tissue was found as compared to proportions in the circulating peripheral blood . We also observed a decreased infiltration of CD8+ T cells as the disease progressed to advanced stage.…”
Section: Discussionsupporting
confidence: 92%
“…Of all these pathological manifestations, fibrosis may be the most typical characteristic of the IFP in OA patients [1]. Histological analyses indicate that the extent of fibrosis in the IFP was higher than that in the SAT [24]. Histological changes, such as IFP fibrosis, may not only be involved in molecular OA processes by changing cytokines production [1,23], but they may also alter the IFP biomechanical properties, thus modifying its ability to absorb gravitational forces exerting on the knee joint, and promoting and perpetuating joint damage [1].…”
Section: Involvement Of Ifp In Koa Pathogenesismentioning
confidence: 99%
“…The immune response is activated following the damage of cartilage. The role of immune responses has been demonstrated in the pathogenesis of OA [24], during which both innate and adaptative immunity may play important roles [36].…”
Section: Immunophenotype Of Immune Cellsmentioning
confidence: 99%
“…Alteration of both conventional and nonconventional Th subsets suggests a role of T cells in OA onset and progression [ 118 ]. A recent paper indicated that in infrapatellar fat pad there is an increase of infiltrating CD8+ T cells that correlates with the radiological score [ 119 ]. B cells, plasma cells, natural killer cells, dendritic cells, and granulocytes are also occasionally present.…”
Section: Low-grade Inflammation In Oamentioning
confidence: 99%